Encyclopedia of Women & Islamic Cultures: Volume 4: Economics, Education, Mobility and Space by Suad Joseph, general editor (Leiden & Boston: Brill, 2007. 587 pages.) (American Journal of Islam and Society, 2009)
An encyclopedia is popularly thought of as presenting the sum of all knowledge,whether it be universal or on a specific topic. A moment’s reflectionreveals, of course, that such an understanding does not quite get at the realconcept, for there is no such thing as “all knowledge.” The historicalmomentwill always define the extent of the knowledge that is available. The structuralterms within which that knowledge is constructed – its headings andsubheadings – are historically bound as well. One of the features – bothadmirable and disconcerting – of the Encyclopedia of Women & IslamicCultures is how the work makes the reader aware of these factors: that thisencyclopedia is, in fact, by its very act of being produced, defining a previouslynon-existent area of encyclopaedic knowledge and that the gaps inknowledge of the subject area, even after the production of the work, are substantial.Volume 4, “Economics, Education, Mobility and Space,” illustratesthis point vividly.As can be seen by the volume’s heading, the overall encyclopedia isorganized at the top level in themes. Within each volume, though, entries areorganized alphabetically. The main topics covered are “Cities,” “Development,”“Economics,” “Education,” “Environment,” “Information Technologies,”“Migration,” “Poverty,” “Slavery,” “Space,” and “Tourism.” Sincethe ordering of the next level of headings is alphabetical as well, there is noparticular organizational logic to the sequence of presentation. Under“Cities,” for example, the subheadings are, in order: “Colonial Cities,”“Homelessness,” “Informal Settlement,” “Islamic Cities,” “Urban BuiltEnvironments,” “Urban Identities,” and “Urban Movements.” It is difficultto ascertain whether any theoretical structure has dictated these subheadings ...